Solve for j 3(6-4j-27j)=10j-31

3(6-4j-27j)=10j-31
Simplify 3(6-4j-27j).
Subtract 27j from -4j.
3(6-31j)=10j-31
Apply the distributive property.
3⋅6+3(-31j)=10j-31
Multiply.
Multiply 3 by 6.
18+3(-31j)=10j-31
Multiply -31 by 3.
18-93j=10j-31
18-93j=10j-31
18-93j=10j-31
Move all terms containing j to the left side of the equation.
Subtract 10j from both sides of the equation.
18-93j-10j=-31
Subtract 10j from -93j.
18-103j=-31
18-103j=-31
Move all terms not containing j to the right side of the equation.
Subtract 18 from both sides of the equation.
-103j=-31-18
Subtract 18 from -31.
-103j=-49
-103j=-49
Divide each term by -103 and simplify.
Divide each term in -103j=-49 by -103.
-103j-103=-49-103
Cancel the common factor of -103.
Cancel the common factor.
-103j-103=-49-103
Divide j by 1.
j=-49-103
j=-49-103
Dividing two negative values results in a positive value.
j=49103
j=49103
The result can be shown in multiple forms.
Exact Form:
j=49103
Decimal Form:
j=0.47572815…
Solve for j 3(6-4j-27j)=10j-31

Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top